Tourism development and its impact on residents' quality of life: the case of Historic City of Melaka, Malaysia / Akmal Adanan, Tania Maria Tangit and Rozman Md. Yusof - Adanan, Akmal; Tangit, Tania Maria; Md. Yusof, Rozman (2012)
This study will examine the impact of tourism development to the residents in one of the Historical City in Malaysia, Melaka; where UNESCO has listed the city as the World Heritage Sites in July 7th, 2008 (UNESCO, 2008). Being among Malaysia's popular heritage destinations, Melaka has received a significant increase of tourist arrivals from 2008 to 2009. The number of tourists have increased by 23.6% from 7,205,492 million (2008) to 9,905,273 million tourists (2009), (Tourism Melaka, 2010). It was observed that the residents in Melaka comprise of different social classes, namely, the upper class, middle class, and lower class. With the influx of tourists, this would possibly generate benefits as well as create problems to the communities in the area.